Fesyen dan Identitas: Simbolisasi Budaya dan Agama dalam Busana Pengantin Jawa Muslim di Surabaya - Meyrasyawati, Dewi (UI Scholars Hub, 2013)
This study is conducted to investigate a popular practice of modifying Javanese bridal costumes based on religious considerations. Transformation from purely traditional Javanese bridal costumes to those with some application of Islamic clothing style is gaining rapid acceptance and begins to be considered as a popular fashion style by a great number of Indonesians, especially in urban areas like Surabaya. The purpose of this study is to discover cultural (Java) and religious (Islam) symbolisms implied in the modification and to examine the signification involved in the process. By applying the fashion system theory, this paper seeks to unravel the symbolisms in modern Javanese-Moslem bridal costumes which reveal a thought system built of two intertwining aspects: Javanese culture and Islamic religious principles. Deep observation into the cultural and religious symbolisms reveals that the modern Javanese-Moslem bridal costumes are actually invented by bridal stylists as a form of capitalism which benefits from a consumerist lifestyle. This fact reflects a shift in the way people signify modern Javanese-Moslem bridal costumes from Javanese local culture to contemporary Javanese culture. Another interesting finding shows that people choose this Javanese-Moslem style for their bridal costumes because of not only religious considerations but also its popularity. The application of Islamic fashion style in the Javanese-Moslem bridal costumes is no longer associated with the obedience to Islamic teachings but is a mere reflection of a growing trend towards more extensive body coverage.